Princesses are not just pretty - Lum, Kate (Bloomsbury, 2014)
"When Princesses Mellie, Allie, and Libby begin to argue about which princess is the prettiest, they decide to hold a contest. But of course, the girls get side-tracked helping others on their way to the contest leaving Princess Mellie as the muddiest, Princess Allie as the yuckiest, and Princess Libby as the drippiest. But due to their kindness, the princesses win in the end"--